Caracterização fenotípica e genotípica de staphylococcus aureus proveniente de leite - Souza, Ayala Oliveira do Vale (2020)
Staphylococcus aureus is a microorganism of importance for public health, due to its predisposition to cause diseases due to the presence of enterotoxins, in addition to presenting cultural resistance to various antibiotics and other virulence factors associated with them, making an individual immune response impossible. Develop an importance of this microorganism in public health, aiming at the characteristic study of phenotypically and genotypically strains of S. aureus, consumption of raw and pasteurized goat and bovine milk from the Central Potiguar region, from August 2018 to April 2019 A total of 168 samples were collected, with 67 samples of pasteurized bovine milk and 19 pasteurized goat milk; 23 samples of raw bovine milk and 59 of raw goat milk. The microbiological analysis performed was detected by Staphylococcus aureus. From the detection and isolation of the typical strains of S. aureus, molecular analyzes were carried out: enterotoxin gene, gene regulators, antibiotic and disinfectant resistance gene and biofilm and antibiogram formation gene. Of the 123 positive responses using the traditional technique, only 14.63% were confirmed by S. aureus. The study carried out to detect antibiotic and disinfectant resistance genes was negative. A search for classic enterotoxins resulted in 11.11% of the samples displayed as a sec genetic encoder, and for non-classic ones, 27.78% contained in the seg gene, followed by 22.23% of the sei gene, and the seh gene with 16, 67 %. Their regulatory genes were also present, with agrI in 61.12% of the strains, agrII in 22.22% and agrIII in 5.56% of the dimensions. For a search for biofilmforming genes, the icaD gene was positive in 100% of S. aureus, accompanied by 11.11% positivity for the icaA gene. Regarding the antibiogram, it was found that 83% of the cephae were resistant to antibiotic oxacillin, and with the exception of one strain, all were resistant to less than one antibiotic. Therefore, S. aureus Purchase raw and pasteurized bovine and goat milk were resistant to antibiotic oxacillin. No antibiotic and disinfectant resistance genes were observed. There was a higher occurrence of non-classical enterotoxins, with emphasis on the genetic coder sec. For the production of a biofilm-forming gene, more evidence was found for the icaD type. The analyzed raw milk proves to be unfit for consumption, as it contains genes that can lead to diseases.